Understanding and Creating Art - Goldstein, Ernest, 1933- (Dallas, Texas : Garrard Publishing Company, Textbook Division, 1986)
Discusses some important paintings and sculpture in terms of design elements and also from the viewpoint of the artist. Includes questions and art activities.
Includes indexes.
Keywords: Composition (Art) -- Juvenile literature; Art -- Psychology -- Juvenile literature; Visual perception -- Juvenile literature; Art appreciation; Composition (Art); Design